PERANCANGAN PROYEK PUSAT KULINER KOTA SOLO DENGAN PENDEKATAN SENSE OF PLACE OLEH KONSULTAN ARSITEKTUR INTERIOR NEO ATELIER - Veronica Nathania Suseno; Astrid Kusumowidagdo (KREASI, 2023)
The final Project Report titled “Solo City Culinary Center Project Design with Approach Sense of Place by Interior Architecture Consultant NEO Atelier” contains the design of the interior architecture project of a restaurant by Interior Architecture Consultant NEO Atelier located at Jl. Yosodipuro no.72, Punggawan, Banjarsari, Surakarta. In this design project, the strategy is used in the sense of place, which will turn into a unique quality and draw for tourists. Sense of place What is presented here is the architectural and cultural aspects of the city of Solo which will provide distinctive characteristics and become a special attraction for visitors. The design’s concept was chosen in response to the client’s requirements. The application of the “Hometown” concept with Kampung Kauman Solo as a reference can be seen in the implementation of shapes, materials, and ornaments applied to the exterior of the building and also the interior of the building. Natural-textured materials are the most commonly used materials in design. To enhance the approach sense of place and create a cozy ambiance reminiscent of my birthplace, A modern design concept served as the basis for choosing colors and materials. The research method used is a qualitative research method by observing the potential that exists around the location. It is so intended that this Final Project Report would aid in describing how a feeling of place is implemented in design projects.